Doppler ultrasound surveillance of TIPS-patency in the era of covered stents – retrospective analysis of a large single-center cohort - Klinger, Christoph; Riecken, Bettina; Müller, Johannes; Westphal, Anja; Löffler, Joachim; Froehlich, Eckhart; Caca, Karel (Zeitschrift für Gastroenterologie, 2018)
Purpose The purpose of this study was to determine accuracy and necessity of long-term Doppler ultrasound (DU) surveillance of transjugular intrahepatic portosystemic shunt (TIPS) patency after implantation of an ePTFE-covered stent-graft (Viatorr).Methods This single-center retrospective study includes 228 consecutive cirrhotic patients with TIPS implantation due to portal hypertensive complications. Standardized DU surveillance was scheduled 3 – 5 days, 3 months, and 6 months after TIPS implantation and every 6 months thereafter. Portal venography was performed in case of DU findings suspicious of TIPS dysfunction, clinical signs of recurrent portal hypertension, or refractory hepatic encephalopathy.Results During a mean follow-up of 16.6 ± 23.4 months, 866 DU examinations were performed. Twenty-two cases of TIPS dysfunction were observed in 16 patients with no first dysfunction more than 4 years after implantation. Routine DU in asymptomatic patients had little therapeutic impact (0.75 %). DU and venography were concordant in 39/46 (84.8 %) paired examinations, and 1-, 2-, and 5-year primary TIPS patency was 87.4 %, 83.7 %, and 79.97 %, respectively. Patients with TIPS dysfunction and subsequent successful revision during the first 2 years of follow-up had a significantly higher risk (p = 0.001) of new dysfunction compared to those without TIPS dysfunction. Cumulative 1-, 2-, and 5-year survival was 68.7 %, 61.3 %, and 42.7 %, respectively.Conclusions Despite acceptable accuracy, scheduled DU surveillance proved to have minor therapeutic impact. Thus, detailed DU surveillance is not useful in asymptomatic patients after 2 years of unremarkable follow-up. In contrast, long-term DU surveilleance should be performed in patients after successful revision of TIPS dysfunction and patients with prothrombotic states (e. g., portal vein thrombosis, Budd-Chiari syndrome).
Keywords: Doppler; Ultraschall; Überwachung; TIPS-Funktion; transjugulärer intrahepatischer portosystemischer Shunt